2014
DOI: 10.1038/nphys2979
|View full text |Cite|
|
Sign up to set email alerts
|

Hierarchy of Hofstadter states and replica quantum Hall ferromagnetism in graphene superlattices

Abstract: In graphene placed on hexagonal boron nitride, replicas of the original Dirac spectrum appear near edges of superlattice minibands. More such replicas develop in high magnetic fields, and their quantization gives rise to a fractal pattern of Landau levels, referred to as the Hofstadter butterfly. Some evidence for the butterfly has recently been reported by using transport measurements. Here we employ capacitance spectroscopy to probe directly the density of states and energy gaps in graphene superlattices. Wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
187
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(207 citation statements)
references
References 35 publications
18
187
1
1
Order By: Relevance
“…We note that around the right corner of the SBZ (labelled as κ ), no conical dispersion is observed, suggesting that the two superlattice valleys κ and κ are inequivalent. Therefore, both the constant-energy maps and the dispersion images presented above reveal directly that SDCs exist at the SBZ corners and only at one of the two superlattice valleys 23 , which is in agreement with the Landau level degeneracy implied from previous quantum Hall effect measurements 5,19 . Such direct information is critical in determining the parameters used to describe the generic band structure of SDCs 10,20 , and in further understanding other experimental results which probe the electronic structure indirectly.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…We note that around the right corner of the SBZ (labelled as κ ), no conical dispersion is observed, suggesting that the two superlattice valleys κ and κ are inequivalent. Therefore, both the constant-energy maps and the dispersion images presented above reveal directly that SDCs exist at the SBZ corners and only at one of the two superlattice valleys 23 , which is in agreement with the Landau level degeneracy implied from previous quantum Hall effect measurements 5,19 . Such direct information is critical in determining the parameters used to describe the generic band structure of SDCs 10,20 , and in further understanding other experimental results which probe the electronic structure indirectly.…”
supporting
confidence: 73%
“…The superlattice potential induced by the lattice mismatch and crystal orientation can significantly modify the electronic properties of graphene and lead to various novel quantum phenomena, for example, the emergence of second-generation Dirac cones (SDCs), which are crucial for the realization of Hofstadter butterfly states under an applied magnetic field 2-5 , renormalization of the Fermi velocity 8,[10][11][12] , gap opening at the Dirac point 4,13-16 , topological currents 15 and gate-dependent pseudospin mixing 17 . Hence, understanding the effects of the superlattice potential on the band structure of graphene is crucial for advancing its device applications, and for gaining new knowledge about the fundamental physics of Dirac fermions in a periodic potential.Previously, the existence of SDCs has been deduced from scanning tunnelling spectroscopy, resistivity and capacitance measurements 2,5,18,19 . However, such measurements are not capable of mapping out the electronic dispersion with momentum-resolved information, and the lack of direct experimental results has led to ambiguous and even conflicting results about the electronic spectra of SDCs and the existence of gaps.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…- 15 and experimentally. [16][17][18][19][20] The earliest experiments on different samples showed conflicting results on the existence of an insulating state at the neutrality point. Some experiments 21 suggested the existence of an electronic gap of about ∼ 30 meV, while others do not see any clear evidence of it.…”
Section: Introductionmentioning
confidence: 99%
“…These crystals engineered with one-atomic-plane accuracy provide unprecedented opportunities to explore unusual properties and new phenomena [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. It was demonstrated that properties of the van der Waals structures depend not only on their building blocks with layer-specific attributes, but also on how the 2D atomic crystals are stacked [12,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%